Formation of artistic orientations of senior pupils in the process of musical-theater activities: methodological aspects - Панькив, Людмила (Pedagogy and Psychology, 2020)
The article highlights the problems of artistic education of high school students in modern conditions. The essence and significance of the artistic orientations of the individual in the context of his spiritual development are considered. Taking into account the age and psychological characteristics of high school students, the role of musical and theatrical activity in the formation of artistic orientations of high school students as a value and selective attitude to art has been substantiated. The pedagogical conditions and methods of the formation of artistic orientations of senior pupils in the process of musical and theatrical activity are revealed. The distinguished methodological aspects of the formation of artistic orientations of senior pupils in the process of musical and theatrical activity are considered as the basis for the effectiveness of pedagogical work in this direction. It has been proved that the formation of the artistic orientations of high school students in the process of musical and theatrical activity opens up new opportunities for art education on the path of the spiritual development of youth.